The Use of An Accounting Information System for Monitoring Website-Based Sales Call Activities in Garment Company - Niko Cahyono Slamet Muljono; G Freddy Koeswoyo; Albertus Dwiyoga Widiantoro (Journal of Business and Technology, 2022)
There are several ways that can be used to increase sales, one of which is using a sales call. At PT. Ricky Mumbul Daya, sales call is one of the main activities carried out to increase sales. Although the process of recording revenues and costs related to sales call activities at that company has used the system, but the process is still not optimal. This is because the data input process is only done by the cashier. Meanwhile, the monitoring process is still done manually. The purpose of this research is to create a Website-Based Accounting Information System for Sales Call Monitoring and tested whether the level of performance and effort expectations of the system has an influence on user behavioral intention. The system development method used is the System Development Life Cycle. Meanwhile, to test the level of the three variables, it will begin with collecting data with a questionnaire and then the data will be analyzed using several testing methods. The result of this research is that the information system created can complete the expected tasks and concluded that the level of performance and effort expectations of the system have an influence on the user’s behavioral intention.